Review: The Destruction of Jerusalem and the Idea of Redemption in the Syriac Apocalypse of Baruch - Lied, Liv Ingeborg (Journal of Semitic studies, 2005)
The Destruction of Jerusalem and the Idea of Redemption in the Syriac Apocalypse of Baruch Rivka Nir , (SBL Early Judaism and its Literature 20). Society of Biblical Literature, Atlanta 2003. viii + 31. Price: $39.95 paperback. ISBN: 1-781983-050-4